Cinanserin reduces plasma extravasation after burn plasma transfer in rats - Hernekamp, Jochen-Frederick; Hu, Sissi Xi; Schmidt, Karsten; Walther, Andreas; Kneser, Ulrich; Kremer, Thomas (Burns, 2013)
Background - Thermal injuries greater than 20% body surface area (BSA) lead to systemic edema and hypovolemic shock. Capillary leakage is induced by different immunomodulative cytokines. Serotonin (5-HT) plays an important role in inflammation, vasodilatation and vasoconstriction and many other pathways such as systemic inflammation in endotoxemia and burns. Cinanserin, a specific 5-HT2 receptor blocking agent was administered to observe whether burn induced systemic edema can be reduced. - Methods - Donor animals underwent thermal injury (100°C water, 30% BSA, 12s) for positive controls and negative controls underwent a shamburn procedure (37°C water, 30% BSA, 12s). Donor rat-plasma was transferred to healthy individuals after bolus injection of Cinanserin (5mg/kg body weight) was performed in recipient animals. Intravital microscopy was performed in mesenteric venules (0/60/120min) to asses systemic edema by FITC-albumin extravasation. Additionally, leukocyte activation (cells/mm2) was observed. - Results - Burnplasma-transfer results in systemic capillary leakage that is not observed in sham burn controls. Intraveneous application of Cinanserin significantly reduces systemic burn edema to shamburn levels. Leukocyte-endothelial interactions are significantly reduced by administration of Cinanserin. - Conclusion - Specific 5-HT2 antagonism reduces systemic burn edema and leukocyte activation after plasma transfer. Reduction of capillary leakage may be partially mediated by leukocyte dependent as well as independent mechanisms. Future studies need to evaluate specific 5-HT2 receptor subtypes to distinguish between local and systemic effects of serotonin antagonists.
Gesehen am 23.04.2021